Dl-3-n-butylphthalide attenuates DOX-induced cardiotoxicity in mice by inhibiting Nrf2/Keap1 complex formation - Yan, Yixiao; Fang, Mingzhen; Zhao, Cong; Lin, Xinru; Tong, Chen; Xiang, Cheng; Ran, Ya; Wang, Xuelian; Li, Shuixin; Chen, Gaozhi; Fu, Lili (Frontiers in Pharmacology, 2025)
IntroductionDrug-induced cardiotoxicity (DICT), defined as myocardial injury caused by direct or indirect toxicity of therapeutic agents, disrupts cardiovascular homeostasis, underscoring the urgent need for preventive strategies in clinical practice. Doxorubicin (DOX), a clinically established anthracycline chemotherapeutic, induces dose-dependent cardiotoxicity driven by reactive oxygen species overproduction. Notably, Dl-3-n-butylphthalide (NBP), a bioactive phytochemical derived from celery, has shown potential in mitigating DOX-induced cardiomyopathy via its antioxidant activity. Therefore, this study aimed to investigate the protective effects of NBP on DOX-induced cardiomyopathy, with a focus on elucidating the underlying mechanisms.MethodWe developed both in vivo and in vitro models of DOX-induced cardiotoxicity. For the animal model, male C57BL/6 mice were administered with DOX (4 mg/kg, i.p.) once a week for 3 weeks. For the cell model, H9C2 myoblasts were exposed to 1 μM DOX for at least 6 h to establish acute cardiotoxicity.ResultsOur results demonstrate that NBP significantly improves cardiac function, as evidenced by approximately 10% increase in cardiac functional parameters (ejection fraction and left ventricular shortening fraction). Besides, NBP exerts favorable effects on cardiac inflammation, apoptosis, fibrosis, and mitochondrial damage both in vivo and in vitro. Further mechanistic investigations revealed that NBP blocks the interaction between Kelch-like ECH-associated protein-1 (Keap1) and Nrf2, thereby preventing the formation of the Nrf2/Keap1 complex.DiscussionThis study indicate that NBP alleviates DOX-induced cardiotoxicity by inhibiting Nrf2/Keap1 complex formation, highlighting its potential as a therapeutic agent for DICT and suggest that Nrf2/Keap1 may be a potential therapeutic target for the management of this condition.